Microfluidic Whispering Gallery Mode Optical Sensors for Biological Applications - Wang, Yuye; Zeng, Shuwen; Humbert, Georges; Ho, Ho‐Pui (Laser & photonics reviews, 2020)
Whispering gallery mode (WGM) resonators have been exploited as a highly sensitive and efficient sensing technique in the past few years. They offer the advantages of ultrahigh sensitivity, compact size, and label‐free sensing capability. More recently, with the rapid development of microfluidic technologies, many integrated WGM sensors, by combining the portability of lab‐on‐chip devices and the high sensitivity of WGM resonators, have emerged. The capabilities of efficient sample handling and multiplexed analyte detection offered by these systems have led to many biological and chemical sensing applications, especially for the detection of single particle or biomolecule. In this review, different sensing mechanisms based on integrated whispering gallery mode resonators are introduced. Various geometries of WGM cavities including solid, liquid, and hollow resonators and a detailed discussion on their integration with microfluidic devices are also covered. Different types of packaging schemes and integration methods are compared in terms of ease of fabrication and device performance. Finally, recent applications of microfluidic‐based WGM sensors for detecting biological and chemical target molecules are discussed, with a prospect on future challenges and trends of development in microfluidics for multiplexed detection. The current state‐of‐the‐art in microfluidic whispering gallery mode (WGM) resonators is reviewed. Different sensing mechanisms and various geometries of WGM cavities are described in detail. Moreover, the latest trends on the integration of WGM resonators with microfluidic devices are introduced. Finally, recent applications of microfluidic‐based WGM sensors for detecting biological and chemical target molecules are discussed.